PENGEMBANGAN LEMBAR KERJA SISWA MODEL KOOPERATIF TIPE NUMBERED HEADS TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR - Wiwin Purwanti; Dian Mayasari; Anis Munfarikhatin (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2021)
The aims of this study were to develop teaching materials of Mathematic Student Worksheets in class VIII SMP using cooperative learning model type Numbered Heads Together (NHT).The type of this research were development with the ADDIE model which were carried out until the implementations and stages due to the COVID-19 pandemic. The Research subject was at SMP Negeri 8 Merauke, in the class VIII by trial sample 6 students with comparison materials. The data collections were carried out through observations, interviews, tests and questionnaires. The results of developing student worksheets are categorized as valid with a percentage value of 95%. The students responses of questionnaire were included in the practical category with an.amount of 81.7%. The teacher response questionnaire included practical criteria with a percentage of 68.75%. The results of learning observations for the first meeting obtained a percentage score of 87%, the second meeting was 80% so that it met the practical criteria. The results of the N-gain test show that student worksheets using the NHT model can improve students achievement.